Petroleum Supply Reforms Could Yield Huge Savings - World Bank (Washington, DC, 2012)
Petroleum supply reforms could yield huge savings. Training flourishes in the informal sector. Credit is a constraint to enterprise development. cAN Africa pay for its universities. How to double Sub-Saharan Africa's agricultural growth rate. Upgrading farming systems in the Sahel. Agricultural research is being revitalized.